Comparative effects of music interventions on depression in older adults: A systematic review and network meta-analysis. (August 2022) - Dhippayom, Teerapon; Saensook, Thitinan; Promkhatja, Natthamon; Teaktong, Thanasak; Chaiyakunapruk, Nathorn; Devine, Beth
Summary: Background: The effect of different music interventions on depression in older adults is varied. We aimed to explore the comparative effect of different music intervention features on depression in older adults. Methods: We searched PubMed, EMBASE, CENTRAL, CINAHL, and ProQuest Dissertations&Theses from inception to October 2021 for randomized controlled trials (RCTs) of music interventions in participants aged ≥60 years. Music interventions were classified based on the TIP (theme, intensity, and provider/platform) framework. The theme was divided into: 1) active music therapy (ACT); 2) receptive music therapy (Recep); and 3) music medicine (MM). The intensity was classified as high (>60 minutes/week), and low (≤60 minutes/week). The provider was classified as a music therapist (MT) or a non-music therapist (NonMT). Summary standardized mean differences (SMD) of level of depression with 95% confidence interval (CI) were estimated using a frequentist framework with a random-effects model. The certainty of evidence was evaluated using the Confidence in Network Meta-Analysis (CINeMA) approach. This study was registered with PROSPERO (CRD42021247165). Findings: Fifteen RCTs involving 1, 144 older adults (mean age 67.9-86.6 years) were included. When compared with usual care, the most effective music intervention was active music therapy >60 minutes/week by music therapist (Act/High/MT) (SMD -3.00; 95%CI, -3.64, -2.35), followed by music medicine >60 minutes/week by non-music therapist (MM/High/NonMT) (SMD -2.06; 95%CI, -2.78, -1.35) with moderate and high certainty of evidence, respectively. Depression scores in older adults treated with ACT/High/MT was also significantly lower than all other interventions, except MM/High/NonMT. Low intensity music interventions other than Act/Low/MT had no impact on depression. Interpretation: Although active music therapy >60 minutes/week by music therapist is the most effective intervention to alleviate depression in older adults, music medicine by listening to music of older adult's own preference >60 minutes/week is an alternative approach in settings with limited resources. Funding: None.